LABORATORY STUDIES OF WATERFLOOD FROM OIL RESERVOIRS IN INDONESIA - Herlan Adim (Testing Center for Oil and Gas LEMIGAS, 1993)
The continual shortage of domestic crude oil requires optimum oil and gas conservation practices to ensure maximum recovery from the reservoirs. Oil production from reservoirs by natural (primary) drive mechanisms is often an inefficient process which may leave considerably more â€œresidualâ€ oil trapped behind the reservoirs than can be produced.